JARODS (JAKARTA ROAD SAGA) MENJELAJAHI JEJAK NAMA JALAN PAHLAWAN UNTUK MEMBANGKITKAN SEMANGAT NASIONALISME DAN MULTIKULTURALISME - Ramadhani, Syafira; Yessino, Salsabilla; Karuniawan, Dwi (Balai Diklat Keagamaan Jakarta, 2024)
Abstract The deterioration of the spirit of nationalism and multiculturalism among young people should be a worry for the entire nation. Teenagers' apathy toward the history of national heroes, as well as their lack of use of technology in learning, necessitated the development of a gaming application called JARODS. The MDLC (Multimedia Development Life Cycle) model with six steps, namely concept, design, material collecting, assembly, testing, and distribution, is used in the game creation study utilizing the RPG Maker MZ program. Material expert validators, application expert validators (Functionality Test), and student respondents from SMPN 4 Jakarta and MAN 3 Jakarta Pusat (Usability Test) are involved in the data gathering process. According to the study findings, the JARODS game application is pronounced legitimate by the material expert with a score 3,71 and it is also declared “valid” in the functionality test. Last, a score ratio was acquired in the usability test on 35 respondents as the topic of the study 3,59 indicating that the game was